Early Experiences with Percutaneous Endoscopic Gastrostomy in Pondok Indah Hospital - Chaidir Aulia; Hermansjur Kartowisastro; Lanny Ch Salim (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Background: Percutaneous endoscopic gastrostomy (PEG) is only recently being introduced in Indonesia with limited clinical experience. Clinical study of patients underwent PEG is very limited. This study was aimed to evaluate clinical profile of patients underwent PEG in a private hospital in Jakarta. Method: A retrospective study was done to patients underwent PEG in Pondok Indah hospital, Jakarta using medical record. Clinical data collected were patients’ demographics, diagnosis of underlying disease, indication for PEG insertion, and follow-up visits. Results: Ten cases were found between 2000 and 2008, six among them were men. All but one cases aged more than 50 years. Ninety percents of the patients had cerebrovascular disorder as their primary diagnosis and 60% of the main indication was dysphagia. Conclusion: No procedure-related major complications and death has occurred. This procedure was safe and potentially be offered to more widely clinical settings. Keywords: dysphagia, percutanelus endoscopic gastrostomy, enteral feeding